HUBUNGAN SENAM OSTEOPOROSIS DENGAN KEJADIAN OSTEOPOROSIS PADA PESERTA SENAM DI RUMAH SAKIT ISLAM SURABAYA - Farida Umamah; Faisal Rahman (Universitas Nahdlatul Ulama Surabaya, 2016)
Gymnastic is important for health. In fact many people who do not do gymnastic for a variety of the reasons. Therefore, the purpose of this study was to find out the relationship between the gymnastic osteoporosis and osteoporosis and osteoporosis in the Surabaya Islamic General Hospital.The design of study was analytic correlational – crosss sectional. The population involved all participant of gymnastic osteoporosis in the Surabaya Islamic General Hospital, totally 55 people, 48 respondents were chosen as the samples by using simple random sampling technique. The independent variabel used in this study was gymnastic osteoporosis and the dependent variabel was the osteoporosis. Questionnaire and bone mass density was used to collect the data which were then analyzed by using Rank Spearman test with the significance level α = 0,05.The resulf of study showed that among 48 respondents almost antirely respondents were (79,2%) Follow exercise according the rules, and most of the respondents (68,8%) osteopenia. Moreover, the result of the statistics test showed that ρ = 0,00 < α = 0,05. So that H0 was rejected which meant that there was a coralation between gymnastic osteoporosis and osteoporosis in the Surabaya Islamic General Hospital.The conclusion is gymnastic beneficial to bone and other health aspec. Gymnastic can be slow the drop of bone mass dencity due to age and increase the general healt, so that decrease osteoporosis.